Modos de ver a iconosfera da arquitetura colonial goiana: cultura visual e processos de mediação na construção de sentidos - Nascimento, Gledson Rodrigues do (2018)
Our objective in this work is to develop an investigation on the ways of seeing the icons of the colonial architecture of Goiás, through processes of mediation between the images produced by us in the historical center of the City of Goiás, and the historiographic visual sources that also report inhabiting in Pirenópolis. The images were produced during our exploratory walks through the colonial street, the historical monuments, the squares and the wide ones of the city of Goiás. As for the city of Pirenópolis, the work was more in charge of the visual sources found in the consulted historiography, that also shows the urbanism Portuguese and their respective characteristics. We believe that the structures used to conduct this research provide both the reader and the researcher with greater ownership of the proposed theme. Thus, initially, we present a conceptual, theoretical and methodological approach, so that soon after, we are embarked by the universe of historiographical images and contextualizations. Following, we present reports about the local Iconsphere, amidst an immersive experience in the historical center of the city, where we identify some buildings in the process of decharacterization and others in a state of ruins in an advanced stage of dilution. However, this architecture and urbanism implanted in the eighteenth century, provide constructions of understandings from the transit of the gaze, revealing nuances that were sedimented with studies in the field of Visual Art and Culture. Particularly with regard to Image Culture and Mediation Processes that marked our eyes towards the Arraial de Sant 'Anna, the Vila Boa, and the City of Goiás, as well as, about the old Half Bridge and the way to live in full XIX century. To a certain extent, these settlements and villages mark the paths of this research, on a way of seeing the colonial architecture of Goiás, through processes of mediation, enabled to construct meanings, from images.